Analisis Strategi Brand Image Kedai Kopi “MOENG KOPI” Melalui Media Sosial Instagram - Alfi Isa Mulyadi; Saifuddin Zuhri (Jurnal Ilmu Komunikasi, 2020)
This article discusses how the strategy for forming a brand image is carried out by the moeng coffee shop, through instagram social media. The research method used in this research is descriptive qualitative method. The results of this study show good results in the formation of Brand Image by applying brand elements and brand image strategy in the Moeng kopi coffee shop. this really helped increase the crowd and the growing recognition of the Moeng coffee shop by a wide audience. The successful establishment of the Brand Image of the Moeng coffee shop is seen from the response of the Customer which showed good results for the Brand Image of the Moeng coffee shop in Surabaya.